Comparison of Strategies to Model Spatial Fluctuations of Room Acoustic Single Number Quantities. Issue 4 (December 2013) - Witew, Ingo B.; Dietrich, Pascal; Pelzer, Sönke; Vorländer, Michael
In a number of independent empiric studies it was shown that room acoustic single number parameters vary severely with small changes of the source and microphone position. Presently there is no evidence that these spatial fluctuations can be modelled using simulated impulse responses. As a result there is limited knowledge about the origin and the contributing influence factors of this variance over space. In this contribution the results of simulations using wave based as well as ray tracing simulations are compared to each other. It will be discussed if these simulations are able to predict the fluctuations that were found in measurement series taken in a number of different auditoria.